2019
DOI: 10.2495/safe190011
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sherpa for the Prevention of Human Errors Among Agricultural Machinery Users

Abstract: Despite the ever stricter safety regulations and standards, the number of accidents in the agricultural sector is still relevant. The reports on occupational accidents in this sector highlight that most serious and fatal accidents are related to both the use of machinery that are not in conformity with safety protection requisites, and their misuse. The present study aims to investigate the latter aspect, focusing on the analysis of human error by means of the Systematic Human Error Reduction and Prediction Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…The review results in Table 3 showed that Italy had the lowest incidence of agricultural injuries. This is in line with Guarascio et al (2019) who discovered that farming injuries tended to decrease, from 50 fatal injuries in 2013 to 28 fatalities in 2019. The results of the review were interesting to explore more about the efforts made by the Italian state; hence, it could reduce the incidence of agricultural injuries that could be applied or modified in other countries, especially Indonesia.…”
Section: Discussionsupporting
confidence: 89%
“…The review results in Table 3 showed that Italy had the lowest incidence of agricultural injuries. This is in line with Guarascio et al (2019) who discovered that farming injuries tended to decrease, from 50 fatal injuries in 2013 to 28 fatalities in 2019. The results of the review were interesting to explore more about the efforts made by the Italian state; hence, it could reduce the incidence of agricultural injuries that could be applied or modified in other countries, especially Indonesia.…”
Section: Discussionsupporting
confidence: 89%
“…Many human error investigation techniques are available for predicting human error in a process in any given domain; however, the consensus among researchers is that the Systematic Human Error Reduction and Prediction Approach (SHERPA) is more effective for exploring human A c c e p t e d M a n u s c r i p t error than such tools as HEIST and Human Error HAZOP (Kirwan, 1992;Salmon et al, 2002). SHERPA was originally created for use in the nuclear power domain (Embrey, 1986) but has been widely used as a human error investigation tool in many other domains (Guarascio et al, 2019;Khandan et al, 2017;Stanton et al, 2002). In particular, it has seen extensive use in healthcare for determining error modes for surgery (Mohammadfam & Saeidi, 2015), addressing errors in medication administration (Lane et al, 2006), or generally investigating care areas such as nursing stations or emergency wards (Ghasemi et al, 2015;Kermani et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Guarascio et.al melakukan penelitiannya dengan berfokus pada analisis kesalahan manusia dengan SHERPA, yang dilakukan terhadap perilaku operator dan persepsi risiko saat melakukan aktivitas pertanian dengan mesin self-propelled yang dikendalikan pejalan kaki. Hasil yang dicapai menunjukkan kurangnya kesadaran keselamatan, terutama di kalangan wiraswasta dan pekerja pertanian paruh waktu, mendorong perlunya upaya yang lebih konsisten untuk meningkatkan informasi dan komunikasi tentang masalah keselamatan di kalangan petani [7].…”
Section: Pengantarunclassified